Globalization or empire? - Nederveen Pieterse, Jan. (New York : Routledge, 2004)
Is America's cultural, economic and military domination of the world globalization, or is it just empire? In this smart, brief book, Pieterse confronts many of the most important issues surrounding this question.
Book Cover; Title; Contents; Introduction; Acknowledgments; References; Neoliberal Globalization; Scenarios of Power; Empire as Metaphor; Neoliberal Empire; Global Inequality: Bringing Politics Back In; Conflict: Technologies of Work, War, and Politics; Globalization North and South; Hyperpower Exceptionalism; Capitalisms: Asian-European Dialogue after Enron; Notes; Bibliography; Index.
Includes bibliographical references (pages 177-189) and index.
Print version record.
eBooks on EBSCOhost
Keywords: United States -- Foreign relations -- 2001-; Balance of power; Imperialism; United States -- Foreign economic relations; Globalization -- Political aspects -- United States; World politics -- 1989-; Équilibre des puissances; Impérialisme.; Mondialisation -- Aspect politique -- États-Unis.; Politique mondiale -- 1989-; États-Unis -- Relations extérieures -- 2001-; États-Unis -- Relations économiques extérieures.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Balance of power; Globalization -- Political aspects; Imperialism; International economic relations; Diplomatic relations; World politics; United States; Imperialismus; Außenwirtschaftspolitik; Globalisierung; Außenpolitik; Gleichgewichtspolitik; USA; Internationalisatie; Neoliberalisme; Imperialisme; Since 1989